Customary Village Responsibility for the Protection of Customer Deposits in Village Credit Institutions in Bali - Putra Krishna Kumara Jaya; I Made Suwitra; I Ketut Sukadana (Inovasi Pratama Internasional. Ltd, 2027)
Customary village responsibility, Village Credit Institutions, deposit protection, and rush money are key issues in the governance of community-based finance in Bali. This article examines the protection of customer deposits in Village Credit Institutions (LPD) and the responsibility of LPD management when simultaneous withdrawals occur. This research applies empirical legal research with statutory, socio-legal, and customary law approaches. Primary data were obtained through interviews at LPD Desa Adat Mengwi, LPD Desa Adat Kesiman, and LPD Desa Adat Semaon, while secondary data were collected from legislation, scholarly literature, and institutional documents. The findings show that customer deposit protection is implemented through internal supervision, external audit, customary village assemblies, liquidity control, and the normative force of awig-awig and pararem. However, the absence of a mandatory and uniform deposit guarantee scheme creates legal uncertainty because customer protection still depends heavily on institutional soundness, customary trust, and the willingness of customary village authorities to intervene. In rush money situations, desa adat functions as an institutional buffer that restores public confidence, mediates disputes, and demands accountability from LPD managers. This article argues that a hybrid protection model is required by combining customary supervision, prudential governance, mandatory LPD-specific deposit guarantee standards, and clear civil or criminal liability for managerial misconduct.